The Influence of Psychological Capital and Perceived Organizational Support on Job Hopping Intention of Generation Z Employees at Conventional Company in Surabaya City - Anastacia, Jesslin; Kustini, Kustini (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
Witnessing the evolving context of the work phenomenon, we can see that the existence of generations has created increasingly complex dynamics. Job hopping has become one of the most prevalent work phenomena among Generation Z. Psychological reasons require generation Z to often reorganize their future job prospects. The expectations that arise in the minds of generation Z employees are related to the role of psychological capital and perceived of organizational support on individual desires to change places (job hopping). This study was created to expand knowledge about the deeper relationship between psychological capital and perceived organizational support on job hopping intention. To obtain information and research data sources, purposive sampling techniques were used and a sample of 145 respondents was then distributed through questionnaire data collection techniques with criteria in the form of generation Z employees who work in conventional companies in the Surabaya City area. The data analysis technique used is Partial Least Square (PLS), where the results show that psychological capital has a negative and significant effect on job hopping intention while perceived organizational support also has a negative and significant effect on job hopping intention. This means that the higher the level of psychological capital and perceived organizational support, the lower the level of job hopping intention of employees.